Reward Sensitivity for a Palatable Food Reward Peaks During Pubertal Developmental in Rats - Friemel, Chris M.; Spanagel, Rainer; Schneider, Miriam (Frontiers in Behavioral Neuroscience, 2010)
Puberty is a critical period for the initiation of drug use and abuse. Because early drug use onset often accounts for a more severe progression of addiction, it is of importance to understand the underlying mechanisms and neurodevelopmental changes during puberty that are contributing to enhanced reward processing in teenagers. The present study investigated the progression of reward sensitivity towards a natural food reward over the whole course of adolescence in male rats (postnatal days 30–90) by monitoring consummatory, motivational behavior and neurobiological correlates of reward. Using a limited-free intake paradigm, consumption of sweetened condensed milk (SCM) was measured repeatedly in adolescent and adult rats. Additionally, early- and mid-pubertal animals were tested in Progressive Ratio responding for SCM and c-fos protein expression in reward-associated brain structures was examined after odor-conditioning for SCM. We found a transient increase in SCM consumption and motivational incentive for SCM during puberty. This increased reward sensitivity was most pronounced around mid-puberty. The behavioral findings are paralleled by enhanced c-fos staining in reward-related structures revealing an intensified neuronal response after reward-cue presentation, distinctive for pubertal animals. Taken together, these data indicate an increase in reward sensitivity during adolescence accompanied by enhanced responsiveness of reward associated brain structures to incentive stimuli, and it seems that both is strongly pronounced around mid-puberty. Therefore, higher reward sensitivity during pubertal maturation might contribute to the enhanced vulnerability of teenagers for the initiation of experimental drug use.